"Gaining Power through Education": Experiences of Honduran Students from High Poverty Backgrounds. Issue 2 (3rd April 2017) - Mather, Peter C.; Zempter, Christy; Ngumbi, Elizabeth; Nakama, Yuki; Manley, David; Cox, Haley
Abstract : This is a study of students from high-poverty backgrounds attending universities in Honduras. Based on a series of individual and focus group interviews, the researchers found students from high-poverty backgrounds face numerous practical challenges in persisting in higher education. Despite these challenges, participants succeeded due to a variety of motivating factors, including commitments to family, community, and country. Participants demonstrated the importance of both strong personal agency and community support in their success.